Pendapatan Dan Nilai Tambah Usaha Kopi Bentenge Di Kecamatan Mallawa Kabupaten Maros - Marhawati, Marhawati; Nurjannah, Nurjannah (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
The purpose of this study was to determine the income and added value generated in the Bentenge Coffee business in Mallawa District, Maros Regency in developing its business so that it can contribute to improving the welfare of the surrounding community. This research is a type of qualitative and quantitative research. Quantitative data was obtained from numbers that were processed using income analysis and added value, while qualitative data was obtained from interviews and observations regarding the condition of the Benteng Coffee business. The analytical method used is the Hayami method. The results showed that the added value generated from the Bentenge Coffee business in Mallawa District, Maros Regency was Rp 36,687.62/kg with a percentage of 50.95% and a profit of Rp 27,217.62/kg with a percentage of 74.18%.